Expiration in the disciplinary proceedings of public servants - Sánchez Pacheco, Diego (Avances en Supervisión Educativa, 2021)
Education inspectors are often appointed to carry out disciplinary procedures against public servants within a limited time so that, once the disciplinary proposal is made, the competent body can decide upon the corresponding disciplinary measure and notify the public servant of such decision in due time and form.In order to guide the task of the appointed public servant, this article aims to analyse the expiration date in disciplinary procedures. In doing so, attention will be paid to the concept, together with the legal changes and present regulation. We will examine the expiration and notification dates in disciplinary procedures, as well as the way such terms are calculated. We shall also study the consequences of solving or notifying a disciplinary procedure out of date. Finally, attention will be paid to common situations which may interrupt or enlarge the date to solve a disciplinary proceeding and the possibility of initiating a new procedure if the expiration has occurred.
Keywords: expiration; disciplinary procedure; prescription; calculation of the term; suspension of the term; pre-judiciality; term extension; proceedings file; file reopening